Uma cerimônia de palavras: a poética biografemática de Sylvia Plath - Derick Davidson Santos Teixeira (2017)
This dissertation is about the links between work and life on Sylvia Plaths writing. Making use of notions such as ecriture and biographeme coined by Roland Barthes, we intend to reach a notion of biographematic poetics. Thereby, following some methodological assumptions of the Brazilian contemporary biographical criticism combined with lacanian oriented psychoanalysis, we intend to contemplate the poets presence at her writing through biographemes.